Behavioral design: A new approach to development policy - Saugato Datta; Sendhil Mullainathan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Successful development programs rely on people to behave and choose in certain ways, and behavioral economics helps us understand why people behave and choose as they do. Approaching problems in development using behavioral economics thus leads to better diagnosis and to better-designed solutions. This paper sketches how to use behavioral insights to design development programs. It distills key insights of behavioral economics into a simple framework about the constraints under which people make decisions. It then shows how this framework leads to a set of behavioral design principles whose use can improve the reach and effectiveness of many development programs.
Keywords: D03; D04; O12; O13; O14; 330; behavioral economics; development; program design